Classification of books at SMP YPK Pematang Siantar using the k-means clustering method - Nani Hidayati; Kasini Kasini (Institute of Computer Science (IOCS), 2023)
The school library is a very important facility in supporting the process of improving the quality of education to produce quality young people. The YPK Pematang Siantar Private Middle School Library has ± 200 book titles in several categories, so that these books can be used optimally there must be a system that regulates the number of book stocks, the number of book loans each month, so that it can be seen which student's reading interest is the most popular in each category . YPK Pematang Siantar Middle School has not implemented an optimal computerized system or everything is still manual. By applying grouping of students' reading interest using the clustering method at SMP YPK Pematang Siantar, it is hoped that the process in the library will be more effective, fast, and precise. Clustering is the most suitable method for optimizing library services. The purpose of this research is to classify which category of books YPK SMP students are most interested in. After calculating the 20 book categories for 3 months, the final result is C1 or the most popular, namely the 3 book categories most in demand. most interested (C2) with 8 book categories, and finally C3 which is less desirable there are 9 book categories. By creating clusters of books which are the most desirable and not desirable, it can improve library services and students' interest in reading and also prevent accumulation of books that are not of interest every year